A numerical study of partitioned fluid‐structure interaction applied to a cantilever in incompressible turbulent flow. (28th November 2019) - Lorentzon, Johan; Revstedt, Johan
Summary: This study presents an approach for partitioned fluid‐structure interaction (FSI) applied to large structural deformations, where an incompressible turbulent solver is combined with a structural solver. The implementation is based upon two different open‐source libraries by using MPI as a parallel communication protocol, the packages and OpenFOAM. FSI is achieved through a strongly‐coupled scheme. The solver has been validated against cases with a submerged cantilever in a channel flow to which experiments, numerical calculations and theoretical solutions are available. The verification of the procedure is performed by using a solid‐solid interaction (SSI) study. The solver has proven to be robust and has the same parallel efficiency as the fluid and the solid solver stand‐alone.